Correlated Between Whitening Cream Mercury Level and Urine Mercury Level Users Whitening Cream in FKM Unair - Fanni Marzela (Universitas Airlangga, 2018)
Whitening cream containing mercury exposure can leads high levels mercury in urine and skin health complained. The aim of this study was to analyze correlation between whitening mercury levels and urine mercury levels among student users whitening cream in FKM Unair. This was a observasional study with cross sectional approach. This study was conducted in 11 undergraduated students of FKM Unair as sample from 12 students who are population by using simple random sampling. Moreover, facial whitening cream measurement used by respondents. Results showed that facial whitening cream as a whole containing mercury with an average 16,325 ppm. Levels mercury in urine of respondents an average 22,455 µg/g creatinin urine. Then the correlated between levels mercury in urine and levels mercury in cream has a value of 0,119. The conclusion of this study is not correlation whitening cream mercury levels with mercury levels in creatinin urine. Users of facial whitening cream is recomended to stop use facial whitening cream containing mercury and replace with natural produk like a mask of the fruit.